Motivating youth engagement in sustainable agriculture: institutional innovations in Andhra Pradesh community-managed natural farming. Issue 7 (3rd October 2022) - Dutta, Deborah; Shambu Prasad, C.
ABSTRACT: This paper highlights ways to address the knowledge–practice gap in the agricultural domain by examining the initiatives of the Community-managed Natural Farming (CNF) Program of the Andhra Pradesh Government in India. The novel initiative to motivate and involve youth known as "Natural Farming Fellows" (NFF), amongst others, has facilitated farmers' transition to sustainable agriculture practices. As agricultural graduates trained in the mainstream knowledge systems of chemical farming, the NFFs journey entails unlearning and learning with farmers. Through interviews with the NFFs, we suggest that such institutional innovations offer newer pathways in managing sustainable transitions.